1993
DOI: 10.1098/rspa.1993.0088
|View full text |Cite
|
Sign up to set email alerts
|

Direct phasing of macromolecular structures by three-beam diffraction

Abstract: Determination of triplet phases of macromolecular structures by means of ψ -scan experiments are reported. The ways in which difficulties can be overcome when investigating macromolecular structures (numerous overlap of multiple beam diffraction profiles, overall weak scattering power and radiation damage) are discussed. It is shown theoretically and experimentally that measurable interference effects exist if the crystal dimensions are smaller than the Pendellösung length. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…One promising physical solution is the multiple-beam Bragg diffraction [6][7][8][9], which is based on the interference among simultaneously excited Bragg reflections. The effect has been shown visible both for small molecule compounds [10,11] and for complex crystals such as quasicrystals [12] and proteins [13,14]. The conventional technique for performing such an experiment involves exciting one Bragg reflection H and then rotating the crystal around the scattering vector H to bring another reflection G into its diffraction condition [15].…”
Section: (Received 24 November 1997)mentioning
confidence: 99%
“…One promising physical solution is the multiple-beam Bragg diffraction [6][7][8][9], which is based on the interference among simultaneously excited Bragg reflections. The effect has been shown visible both for small molecule compounds [10,11] and for complex crystals such as quasicrystals [12] and proteins [13,14]. The conventional technique for performing such an experiment involves exciting one Bragg reflection H and then rotating the crystal around the scattering vector H to bring another reflection G into its diffraction condition [15].…”
Section: (Received 24 November 1997)mentioning
confidence: 99%
“…and (3) Triplet phases (TP's) can be determined from 3-beam diffraction experiments with protein crystals [1]. We are investigating the potential for using such measurements in combination with direct methods to solve protein structures.…”
Section: Ps020909 Molecular Replacement: a New Den-sity Modificatiomentioning
confidence: 99%
“…This fact constitutes the so-called X-ray phase problem in diffraction and scattering experiments (Lipscomb, 1949;Hauptman & Karle, 1953;Giacovazzo, 2002;Giacovazzo et al, 1992). Recent development of multiple diffraction techniques has shown that the phase of a structure-factor triplet can be determined quantitatively from the intensity of three-wave diffraction in a crystalline material system under resonance or non-resonance conditions (Miyake & Kambe, 1954;Ewald & Hé no, 1968;Colella, 1974;Post, 1977;Chapman et al, 1981;Chang, 1982;Juretschke, 1982;Hü mmer & Weckert, 1990;Chang et al, 1991;Weckert et al, 1993;Weckert & Hü mmer, 1997;Chang et al, 1998;Shen, 1998Shen, , 1999Stetsko et al, 2001;Morelhã o & Kycia, 2002). As an initial experiment, we have selected the well known silicon crystal and investigated the phase change due to laser excitation in a few hundred picoseconds in relation to the redistribution of the averaged covalent electron density under quasi-thermodynamic equilibrium.…”
Section: Introductionmentioning
confidence: 99%